Self‐Sustained Marangoni Flows Driven by Chemical Reactions. Issue 6 (19th October 2021) - Nguindjel, Anne‐Déborah C.; Korevaar, Peter A.
Abstract: The front cover artwork is provided by Anne‐Déborah Nguindjel and Peter A. Korevaar, Radboud University. The image represents the concept of self‐sustained Marangoni flows. These flows bring the fuel to the reaction center, to keep the flow "alive" in its out‐of‐equilibrium state.. Read the full text of the Article at 10.1002/syst.202100021 . Abstract : "The coupling between a set of chemical reactions and a physical phenomenon like the Marangoni effect can lead to an emerging out‐of‐equilibrium system. The surface tension of the air–water interface was manipulated by using photochemistry to create a Marangoni flow that keeps itself 'alive' by delivering reagents to the reaction site…" This and more about the story behind the front cover can be found in the Article at 10.1002/syst.202100021 .